The Experience of Jewish Liturgy : Studies Dedicated to Menahem Schmelzer. - Blank, Debra Reed (Brill reference library of Judaism ;, 2011)
This edited collection honors Menahem Schmelzer's influence upon the field of Jewish liturgy. Three generations of scholars apply different analytical methods to varying texts and ritual occasions, providing an up-to-date picture of the field and its implications for related areas.